Some Trends in Publishing in Continuing Education in Sub-Saharan Africa. - Adekanmbi, Gbolagade (International Journal of the Book, 2011)
Africa has had a pitiable record in its publishing output, generally considered the lowest in the world. UNESCO book publishing statistics for 2010 indicate that no African country appears in the first 37 countries listed in the order in which they have published books. The statistics on youth and adult literacy, secondary school enrolment, gross enrolment ratio at the tertiary level, and the continent's digital readiness paint a gloomy picture. In the field of continuing education, the dearth of book publishing has been observed. Most of the major books and journals used in the field are published abroad. Africa thus relies extensively on the published works from outside the continent. This paper discusses the state of adult and continuing education on the continent. It examines some publishing trends on the continent in the field of continuing education and highlights some good pratices in Europe and the USA which African publishers could replicate. It also suggests ways by which publishing could be enhanced especially by universities, continuing education associations and other organisational providers of continuing education.